Soft skills elements in structured clinical skill assessment: a qualitative study - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Ahmad, Norfadzilah; Muhammad, Siti Aesah @ Naznin; Chan, Chong Mei (DiscoverSys Inc., 2022)
Introduction: The intangible nature of soft skills makes it difficult for nursing academics to evaluate nursing students’ attainment of these skills. Most of the time, academics focus more on assessing nursing students’ knowledge and performance (hard skills) in clinical skill assessments. In focusing primarily on assessing nursing students’ hard skill competencies, the nursing profession has given inadequate attention to developing their soft skill competencies. Thus, this study aimed to explore the nursing academic’s view on soft skills elements in structured clinical skill assessment for the undergraduate nursing program. Method: This study was conducted using a qualitative approach. A total of 10 nursing academics were involved, and they were recruited through a purposive sampling method. Data was collected through in-depth interviews using open-ended questions to gain insight into nursing academics’ perception of soft skills elements in structured clinical skill assessment for the undergraduate nursing program. Data analysis was conducted by using an inductive content analysis method. Results: Four themes emerge from this study. These are 1) awareness and involvement, 2) Factors influencing on implementation of soft skills in the structured clinical skills assessment, 3) academic responsibility, and 4) suggestions to overcome barriers. Conclusion: Findings from this study provide new insights into the nursing academic perception of soft skills elements in structured clinical skill assessments of undergraduate nursing program needs improvement and proper structure on how/what are the soft skills elements that want to measure for nursing students. These findings would assist in developing a more strategic framework for soft skills elements in structured clinical skill assessments to produce quality nursing graduates